2013
DOI: 10.1371/journal.pone.0077239
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Synonymous Codon Choice in the Translation Initiation Region of Dengue Virus

Abstract: Dengue is the most common arthropod-borne viral (Arboviral) illness in humans. The genetic features concerning the codon usage of dengue virus (DENV) were analyzed by the relative synonymous codon usage, the effective number of codons and the codon adaptation index. The evolutionary distance between DENV and the natural hosts (Homo sapiens, Pan troglodytes, Aedes albopictus and Aedes aegypti) was estimated by a novel formula. Finally, the synonymous codon usage preference for the translation initiation region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…To determine the influence of the overall codon usage of hosts on that of ZIKV, the similarity index D(A , B) [26] was calculated as follows: where R(A , B) is termed as a cosine value of an included angle between A and B spatial vectors and represents the extent of similarity between ZIKV and hosts in the aspect of overall codon usage pattern. a i is defined as the RSCU value for a specific codon among 59 synonymous codons in ZIKV polyprotein-coding region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the influence of the overall codon usage of hosts on that of ZIKV, the similarity index D(A , B) [26] was calculated as follows: where R(A , B) is termed as a cosine value of an included angle between A and B spatial vectors and represents the extent of similarity between ZIKV and hosts in the aspect of overall codon usage pattern. a i is defined as the RSCU value for a specific codon among 59 synonymous codons in ZIKV polyprotein-coding region.…”
Section: Methodsmentioning
confidence: 99%
“…b i is defined as the RSCU value for the same codon of ZIKV’s hosts. D(A , B) represents the potential effect of the overall codon usage of the hosts on that of ZIKV, and its value varies from 0 to 1 [26]. The higher D(A , B) means the stronger influence of environment related synonymous codon usage patterns of hosts on that of ZIKV.…”
Section: Methodsmentioning
confidence: 99%
“…To date, analyses of Flavivirus codon usage are fragmentary, and such studies have primarily focused on particular virus species, as previously described (Hu et al, 2011;Moratorio et al, 2013;Zhou et al, 2013). Conversely, the evolutionary characteristics and genetic relationships of codon usage bias in the TMUV genome have not been systematically studied; indeed, only a few genomic sequences of TMUV have been sequenced to date, with many studies only recently performed.…”
Section: Discussionmentioning
confidence: 99%
“…For viruses, little information exists regarding the extent and origin of synonymous codon variation. Recent efforts to elucidate codon usage biases in Flaviviridae have concentrated mainly on Dengue virus (DGV) (Zhou et al, 2013), West Nile virus (WNV) (Moratorio et al, 2013), and Hepatitis C virus (HCV) (Hu et al, 2011). In contrast, investigations of TMUV have primarily focused on viral isolation and identification Tang et al, 2013a), the establishment and application of diagnostic methods (Li et al, 2012b;Yun et al, 2012), and genetic analyses of complete genome sequences Wan et al, 2012;Zhu et al, 2012), whereas information regarding codon usage patterns is not available.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zhou et al reported no link of geographic origin to the codon usage of DENV [13]. Behura and Severson found that the silent sites are favoring the geographical diversification [15].…”
Section: Discussionmentioning
confidence: 99%